DHARMA YUDHA KARMA DALAM KITAB SUCI BHAGAVADGITA - Ida Bagus Putu Eka Suadnyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
In the holy book of Bhagawad Gita that is one of Hindu’s holy book that assumed as pancamo weda. In the holy bookk of Bhagawad Gita, there are eighteen chapter which is unity that in each chapter contents holy teaching that should as guidance in human life. One of lesson that written in the holy book is Dharma Yudha Karma that written at chapter II that is Samkhya yoga? At this lesson assumed important explored its existence and how is the form of this lesson. There are some function of lesson of Dharma Yuda Karma that are spiritual function and improvement on life quality through incline of spiritual that have important position in the society. There are some education value that contents inside as follows ethic education value, ritual education value and tattwa education value that taken from Hindu’s doctrine self.